Optimalisasi Pemberdayaan Sumber Daya Lahan Berbasis Kearifan Lokal dalam Mendukung Ketahanan Pangan yang Berkelanjutan Melalui Taman Edukasi Green House - Fina Firdiyanti; Ajeng Pramesthy Hardiani Kusuma; Mahasiswa KKN Kolaboratif 168 (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Environmentally friendly agriculture is an increase in food production followed by environmental sustainability which is the principle of implementing a sustainable environmentally friendly agricultural system. The issue of eco-friendly agriculture involves order in maintaining sustainable agricultural production while maintaining environmental sustainability. The use of pesticides and chemicals in agriculture can have negative impacts on the environment, including water, soil and air pollution. Solutions to this involve using organic farming practices, integrated pest management, and crop diversification to reduce dependence on pesticides. The potential for resilience and local wisdom owned by the Kertosari Village Community is the main capital in developing an educational park area to improve welfare and independence. The purpose of this service is to create a sustainable community empowerment model based on food security and local wisdom in developing agro-tourism.